The Effect of Cooperative Model Type Team Assisted Individualization (TAI) on Student Learning Outcomes in Integrated Thematic Learning - Putri, Sonia Dwi Permata; Fitria, Yanti (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
The main objective of this study is to identify the impact of Team Assisted Individualization models on the academic results of primary school students on the topic "environment is our best friend." The above research was quantitative and employs a quasi-experimental situation design. The design of a non-equivalent Control Group is being used in the study. The grouping sampling method had been used to sample the population, which was composed of 3 SD in Cluster I, Kec. IV, Jurai. The study was undertaken at Class VA had 16 students in it as an experiment group and Class VB had 15 students in it as a control group. Preconditioned test results in the form of normality, homogeneity tests, and hypothetical tests using the t-test were also used to analyze the data for this research. The experimental class's pre-test average was 46,25, and the post- test average was 80,5 after implementing the Team Assisted Individualization learning models. Meanwhile, after being taught using the traditional approach of 64,13, the control class received an average of 49,06 There is a pre-test and a post-test. Then there's the t- test both had a significant level of 0,05. This ttable = 2,045 > tcount = 3,605. It can be concluded that the Team Assisted Individualization model has an impact on students' learning outcomes when it comes to the topic "environment is our best friend.